The bookbinder's guide to love - Garbera, Katherine (Harlequin, Afterglow Books, 2024)
"As a lonely foster kid, Serafina Conte sought refuge in handmaking journals...Now, in the quirky new age store she shares with her two best friends, Sera's intentions have paid off. Her journals are in the spotlight--and rumored to manifest great things...After the death of her mentor, Ford Sitwell, all the loneliness and insecurity of her past returns. The only balm is the box of antique books he left to her. But Ford's suspicious brooding grandson, Wes, is ready to think the worst of her--and get his grandfather's books back! The first part doesn't bother her. The second? Forget it. Sera won't give Wes the books so easily. But it's clear he's seeking something more, an emotional connection no book can replace"--